The epidemiology of primary headaches in patients with multiple sclerosis - Long Wang; Juan Zhang; Zi‐Ru Deng; Mei‐Dan Zu; Yu Wang (Brain and Behavior, 2021)
Abstract Objective Recent studies have shown a pathophysiologic link between headache and multiple sclerosis (MS), but the prevalence of primary headaches among patients with MS differs substantially across studies. This meta‐analysis aimed to comprehensively gather available evidence to estimate the prevalence of primary headaches among patients with MS. Method We systematically searched the electronic databases including PubMed, Embase, and Scopus for cohort, case–control, cross‐sectional studies that measured the prevalence of headache among patients with MS. Two reviewers independently screened titles and abstracts to identify the eligible studies and the full texts of the included studies were reviewed. Newcastle‐Ottawa Scale (NOS) was used to assess the risk of bias of the included literatures. We then conducted a meta‐analysis using Stata Software 15.0 to calculate the pooled prevalence of headaches among patients with MS and assess the source of heterogeneity. Results We identified 16 eligible studies covering a total of 3,560 patients with MS. The pooled estimated prevalence of primary headaches among patients with MS was 56%. The statistical heterogeneity was moderate with I2 of 82.1% (p < .001). Both a visual inspection of the funnel plot and Egger’ regression tests revealed no significant publication bias (p = .44). The pooled estimated prevalence of migraine (55%) was higher in comparison with that of tension‐type headache (20%). The prevalence of migraine subtype was 16% and 10% for migraine without aura and migraine with aura, respectively. The pooled prevalence of primary headache in case–control group (57%) was approximately in line with the cross‐sectional group (56%). Conclusion The overall prevalence of primary headaches among patients with MS was considerably high. Clinical screening of headache among patients with MS will be helpful to formulate an individualized treatment plans and alleviate the physical and mental impact of the disease.